Flower-like gold nanoparticles labeled and silver deposition rapid vertical flow technology for highly sensitive detection of Brucella antibodies. Issue 17 (2nd August 2021) - Fang, Ashe; Sun, Yixiao; Feng, Danni; Ma, Mingze; Xu, Zhihua; Zhang, Tieying; Shi, Feng
Abstract : In this rapid vertical flow technology, flower-like gold nanoparticles were coupled with Staphylococcus aureus protein A to detect brucellosis antibodies, and silver deposition amplification technology was used to improve the sensitivity. Abstract : To prevent the transmission of brucellosis, rapid vertical flow technology (RVFT) was developed to detect brucellosis antibodies. To improve the sensitivity of the technique, lipopolysaccharides (LPS) were purified and used to detect brucellosis antibodies. To improve the sensitivity of serum antibody detection, a single multifunctional buffer was established in whole blood and other biological samples, and the advantages of the lateral flow immunoassay were retained. Flower-like gold nanoparticles were applied to RVFT for the first time. In this study, silver ions were catalyzed by flower-like gold nanoparticles into metal silver deposited on the surface of gold nanoparticles for the first time, which not only increased the particle size of gold nanoparticles, but also showed a more distinguishable black color on the test zone, further improving the sensitivity of RVFT. Standard Brucella -positive serum (containing Brucella antibody at 4000 IU mL −1 ) could be detected in this system even for a dilution factor of 2 × 10 −3 . The detection limit was 2 IU mL −1 . RVFT can effectively avoid the false negative phenomenon in lateral flow immunoassay. RVFT is simple to operate, with a short reaction time, 2–3 minutes visible to the naked eye, without any equipment. Because it is very important to control the brucellosis epidemic, this approach has great application prospects in basic medical units and for veterinarians.